Descomposición de procesos de incrementos independientes en casi intervalos - Jaime Lobo Segura (Revista de Matemática: Teoría y Aplicaciones, 2009)
We introduce the notion independent increment in quasi-intervals. Some properties of the fixed points of these processes are studied, as well as those of the aditive descomposition. Finally, we establish the relation between this concept with the classical one and we deduce a property of the total variation of continuous-time processes.